The role of BCL-2 family proteins in regulating apoptosis and cancer therapy - Qian, Shanna; Wei, Zhong; Yang, Wanting; Huang, Jinling; Yang, Yinfeng; Wang, Jinghui (Frontiers in Oncology, 2022)
Apoptosis, as a very important biological process, is a response to developmental cues or cellular stress. Impaired apoptosis plays a central role in the development of cancer and also reduces the efficacy of traditional cytotoxic therapies. Members of the B-cell lymphoma 2 (BCL-2) protein family have pro- or anti-apoptotic activities and have been studied intensively over the past decade for their importance in regulating apoptosis, tumorigenesis, and cellular responses to anticancer therapy. Since the inflammatory response induced by apoptosis-induced cell death is very small, at present, the development of anticancer drugs targeting apoptosis has attracted more and more attention. Consequently, the focus of this review is to summarize the current research on the role of BCL-2 family proteins in regulating apoptosis and the development of drugs targeting BCL-2 anti-apoptotic proteins. Additionally, the mechanism of BCL-2 family proteins in regulating apoptosis was also explored. All the findings indicate the potential of BCL-2 family proteins in the therapy of cancer.